Improving the mental health and mental health support available to adolescents with social care-experience via low-intensity life story work: a realist review protocol. Issue 3 (9th March 2022) - Hammond, Simon P; Duddy, Claire; Mickleburgh, Ella; Hiller, Rachel; Neil, Elsbeth; Williams, Kevin; Rodgers, Luke; Wilson, Jon; Wong, Geoff
Abstract : Introduction: Adolescents are the fastest growing group entering social care and are most at risk of mental ill-health. Life Story Work (LSW) is an existing transdiagnostic intervention thought to improve the well-being and mental health of children and adolescents under the care of a local authority by assisting the processing of trauma. Yet LSW is poorly evidenced, lacks standardisation and focuses on younger children. LSW is also high-intensity, relying on specialist input over several months. Adolescent-focused low-intensity-LSW is a promising alternative. However, there is poor evidence on how LSW, let alone low-intensity-LSW should be delivered to adolescents. We aim to identify why, how, in what contexts, for whom and to what extent low-intensity-LSW interventions can be delivered to adolescents with care-experience. Methods and analysis: Undertaking a realist review, we will: (1) develop an initial programme theory (PrT) of adolescent-focused low-intensity-LSW by consulting with two key expert panels (care-experienced and professional stakeholders), and by searching the literature to identify existing relevant theories; (2) undertake a comprehensive literature search to identify secondary data to develop and refine our emerging PrT. Searches will be run between 12/2021-06/2022 in databases including MEDLINE, PsycINFO, ASSIA and relevant sources of grey literature; (3) select, extract and organise data; (4) synthesise evidence using a realist logic of analysis and undertake further iterative data searching and consultation with our expert panels; (5) write up and share the refined PrT with our expert panels for their final comments. From this process guidance will be developed to help improve the delivery of LSW to support the mental health needs of adolescents with care-experience. Ethics and dissemination: Ethical approval is not required. Dissemination will include input from expert panels. We will develop academic, practice and youth focused outputs targeting adolescents, their carers, social, healthcare, and educational professionals, academics, and policymakers. PROSPERO registration number: CRD42021279816.